Design of all-optical read-only memory - Jung, Young Jin; Park, Namkyoo; Jhon, Young Min; Lee, Seok (OPTICAL SOC AMER, 2009)
A semiconductor optical amplifier-based all-optical read-only memory ( ROM) is successfully demonstrated through simulations using a one-level simplification method optimized for optical logic circuits. Design details are presented, and advantages are discussed in comparison with an all-optical ROM-employing decoder. We demonstrate that eight characters can be stored at each address in the American Standard Code for Information Interchange. (C) 2009 Optical Society of America
Keywords: CROSS-GAIN MODULATION; AMPLIFIERS; MODEL